Analisis Pengendalian dan Penanganan Non-Performance Financing pada PT BPRS Bumi Rinjani Batu - Abdul Wahid Mahsuni (Jihbiz : Jurnal Ekonomi, Keuangan dan Perbankan Syariah, 2018)
The purpose of this research is to analyze the process operation of defrayal which is conducted by PT BPRS Bumi Rinjani Batu in channeling of defrayal between shahibul mal and mudharib. And alsoto analyze the handling which have been done by PT BPRS Bumi Rinjani Batu to non-performing financing that happened during period 2014-June 2016. According to the Bank of Indonesia criterion, the amount of NPF consists of credit less fluent hesitated and stock. NPF in PT BPRS Bumi Rinjani Batu isn't exceeded from specified rule by the Bank of Indonesia means the NPF there during 3.5 the last years less than 5%. It’s proven that in 2015 the NPF is 1.9% in 2014 is 0.75% in 2015 is 0.99% and in June 2016 is 0.9%. The handling has been done by PT BPRS Bumi Rinjani Batu depends on the weight and the light of the problem. For the heavy category, the bank will do abolition and in the light category, the bank will do revitalization.